2020
DOI: 10.15252/embj.2020105499
|View full text |Cite
|
Sign up to set email alerts
|

Rabl2 GTP hydrolysis licenses BBSome‐mediated export to fine‐tune ciliary signaling

Abstract: Cilia of higher animals sense various environmental stimuli. Proper ciliary signaling requires appropriate extent of BBSome‐mediated export of membrane receptors across ciliary barrier transition zone (TZ) through retrograde intraflagellar transport (IFT) machinery. How the barrier passage is controlled, however, remains unknown. Here, we show that small GTPase Rabl2 functions as a molecular switch for the outward TZ passage. Rabl2‐GTP enters cilia by binding to IFT‐B complex. Its GTP hydrolysis enables the ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(90 citation statements)
references
References 75 publications
8
79
1
Order By: Relevance
“…And like TULP3, RABL2 is required for targeting ciliary GPCRs such as HTR6 and GPR161 ( 31 ). Recently, RABL2 has also been implicated in BBSome-dependent ciliary GPCR exit ( 49 ). Our binding experiments indicated that RABL2 interacts with both HTR6-IC3 and HTR6-CT, and that binding to HTR6-IC3 is dependent on CTS1 residues, whereas binding to HTR6-CT does not require CTS2 residues ( Figs 12A–C and S7 ).…”
Section: Discussionmentioning
confidence: 99%
“…And like TULP3, RABL2 is required for targeting ciliary GPCRs such as HTR6 and GPR161 ( 31 ). Recently, RABL2 has also been implicated in BBSome-dependent ciliary GPCR exit ( 49 ). Our binding experiments indicated that RABL2 interacts with both HTR6-IC3 and HTR6-CT, and that binding to HTR6-IC3 is dependent on CTS1 residues, whereas binding to HTR6-CT does not require CTS2 residues ( Figs 12A–C and S7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Through its effects on ciliary entry and exit, RABL2 also regulates ciliary GPCR trafficking. Ciliary levels of GPCRs, including HTR6, are reduced by RABL2 siRNAs, whereas overexpression of GTP-locked RABL2-Q80L increases ciliary GPCR accumulation [61,62,68]. Furthermore, HTR6 and other ciliary GPCRs interact with RABL2, regardless of GTP status, as opposed to IFT-B, which specifically interacts with GTP-bound RABL2 [61,62,64].…”
Section: Role Of Rabl2 In Htr6 and Sstr3 Ciliary Targetingmentioning
confidence: 97%
“…RABL2 is a small GTPase whose GTP-bound form, resulting from RABL2's intrinsic guanine nucleotide exchange activity, is recruited by CEP19 to the distal mother centriole, where RABL2-GTP recruits its effector, the IFT-B holocomplex, with which RABL2-GTP is subsequently released into the cilium to initiate anterograde IFT, thus promoting ciliogenesis and ciliary protein entry [61,62,64]. Once inside cilia, GTP hydrolysis is required for RABL2 dissociation from IFT-B, and for BBSome-dependent ciliary exit [68]. Accordingly, RABL2-null mice display a BBS-like phenotype [61,64,68].…”
Section: Role Of Rabl2 In Htr6 and Sstr3 Ciliary Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…The model does not exclude that adapter-cargo interactions are regulated as well. Binding of the BBSome to IFT trains is regulated by three small GTPases, IFT22, IFT27 and RabL2 and BBSome-dependent export requires ubiquitination of its GPCR cargoes (EGUETHER et al 2014;DESAI et al 2020;SHINDE et al 2020;XUE et al 2020;DUAN et al 2021). Functional analysis of the phosphorylation sites in the unordered region of ARMC2 could provide insights into the regulation of IFT-ARMC2-RS interactions.…”
Section: Ift Of Large Axonemal Complexes Involves Adaptersmentioning
confidence: 99%